Introduction: Law & The New Institutional Economics - John N. Drobak (Washington University Journal of Law & Policy, 2008)
The Articles in this symposium are examples of legal scholarship in the new institutional economics (“NIE”). The new institutional economics takes its name from institutions: the rules that structure the economic, political, and social interactions in a society. Institutions can be formal, such as law, or informal, such as social norms. The new institutionalists believe that economic performance cannot be understood without paying attention to institutions. Consequently, their scholarship examines a multitude of economic and political issues by focusing on institutions. Law in its various forms (constitutions, statutes, common law, contract terms, etc.) is the most important and prevalent type of formal institution, so the focus on institutions is often a focus on the law. To many new institutionalists legal issues are at the core of their scholarship, as this symposium will illustrate.
Keywords: Institutional investments; Law & amp; economics; Law – Study & amp; teaching; New institutional economics (NIE); Institutions; Economics; Neoclassical price theory; Argentina; Property rights; Water – Law & amp; legislation; China